Development of a Social-Emotional Counseling Module for Elementary School Guidance and Counseling Teachers in Supporting Students’ Mental Health - Fitriyanti Sulaiman; M. Yunus Sudirman; Suparman Suparman; Windah Windah; Putriyani Putriyani (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
The high prevalence of social anxiety, tantrum behavior, and social withdrawal among elementary school students in Enrekang Regency indicates the urgent need for structured and contextual preventive counseling interventions. This study aimed to develop a culturally based Social-Emotional Counseling Module (SECM) that is valid and effective in improving students’ social-emotional competence and emotional well-being. The study employed a modified Borg and Gall Research and Development model consisting of eight stages. Expert validation indicated a very high validity level (S-CVI = 0.92). The implementation involved seven guidance and counseling teachers and 32 students in grades 4–6 from five elementary schools using a one-group pretest–posttest design. Data were collected through the SECQ, SASC, and CORS instruments. The findings revealed significant improvements in overall social-emotional competence (t(19) = 6.21, p < 0.001, d = 1.39), emotional well-being (t(19) = 6.44, p < 0.001, d = 1.44), and approximately 20% reductions in social anxiety and tantrum behavior. These findings indicate that the SECM is an effective, contextual, and replicable preventive intervention for elementary schools.